Optimalisasi Program Makan Bergizi Gratis di SMK Negeri 1 Jember dalam Rangka Peningkatan SDM Unggul Masa Depan - Ciplis Gema Qori'ah; Yulia Indrawati; Oktaviani Ari Wardhaningrum; Misbahol Yaqin; Catur Wulandari, Meisyaroh; Bayu Wijayanti (Jurnal Pelayanan Masyarakat, 2025)
This community service activity aims to optimize the Free Nutritious Meal Program (MBG) at SMK Negeri 1 Jember as an effort to improve the quality of human resources and student productivity. The main problems identified include low nutritional literacy, undeveloped healthy consumption habits, and weak synergy between schools, families, and local food businesses. The community service was implemented using the Participatory Rural Appraisal (PRA) approach through the Plan, Act, Observe, and Reflect stages, involving teachers, students, parents, and SPPG. The results of the activity showed an increase in the knowledge and skills of school residents regarding nutrition management and food safety, the formation of a healthy consumption culture, and the strengthening of the nutritious food supply chain involving MSMEs and local farmer groups. In addition, collaboration between parties has become more solid, thus supporting the program. This activity demonstrates that the participatory approach can strengthen the institutional capacity of schools while serving as a model for implementing adaptive and replicable nutrition programs for other educational institutions.